Pengembangan Web Digital Berbasis Google Site “Bakti-Ku” pada Pembelajaran PAI Kelas 4 SD - Assidiqi, Asepta; Salmawati, Anisa; Anatasya, Neng Wulan; Aeni, Ani Nur (YASIN, 2025)
The use of digital learning media is increasingly widespread in the field of education, including in the teaching of Islamic Religious Education (PAI) in traditional classrooms. The aim of this research is to develop interactive and easily accessible digital learning materials using Google Sites that can be utilized by teachers and students. The research and development (R&D) method employed is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The findings of the research indicate that the web-based learning materials used received positive responses from both educators and students. The validation tests conducted by media experts and content experts demonstrate that this media meets very good feasibility standards. Furthermore, the use of media in classroom learning has a positive impact on students' understanding of PAI material. Thus, this web-based digital learning media can serve as an effective alternative in supporting the learning process in elementary schools.